Mandibular reconstruction by fibula graft: A report on two cases - Zango Adama; Belem Ousmane; Ili Bievenda Vincent; Millogo Mathieu; Idani Motandi; Badini Soutoungnoma Ahmed Patrick; Yanogo Wendpouiré Armel Aristide; Konsem Tarcissus (Elsevier, 2023)
Mandibular bone loss represents an acquired bone destruction leading to a permanent continuity solution of the mandible. Mandibular reconstruction with fibular grafting is an effective alternative to restore bone continuity and ensure the aesthetic and functional functions of the patient. Two cases of successful mandibular reconstruction with the fibular graft were presented at the Department of Stomatology and Maxillofacial Surgery of the Yalgado Ouédraogo University Hospital (CHUYO). The first case concerns a 34-year-old female patient who underwent an interrupted mandibular resection for an ossifying fibroma. The second patient was a 38-year-old man with an ameloblastoma of the horizontal branch of the mandible who underwent hemi-mandibulectomy. A splint was placed for both patients. Mandibular reconstruction with a fibular bone graft taken from the left leg was performed in a second stage. The postoperative course was simple. Surgical follow-up noted good integration of the graft into the recipient site. The results obtained were satisfactory for each patient in terms of function (mastication, swallowing, phonation) and aesthetics. A study of the morphological data of the mandible would be of great help in producing a cutting guide that takes into account the realities of our populations.